2021
DOI: 10.1093/braincomms/fcab092
|View full text |Cite
|
Sign up to set email alerts
|

Prion potentiation after life-long dormancy in mice devoid of PrP

Abstract: Prions are neurotropic pathogens composed of misfolded assemblies of the host-encoded prion protein PrPC which replicate by recruitment and conversion of further PrPC by an autocatalytic seeding polymerization process. While it has long been shown that mouse-adapted prions cannot replicate and are rapidly cleared in transgenic PrP0/0 mice invalidated for PrPC, these experiments have not been done with other prions, including from natural resources, and more sensitive methods to detect prion biological activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 87 publications
4
9
0
Order By: Relevance
“…The modified RT-QuIC protocol with substrate replacement used here allowed us to ensure the availability of rPrP substrate for a longer period of time to enable the detection of low levels of prion seeding activity that would have been missed otherwise. Positive seeding activity observed in the brain of 77.7% of Wisc-1-tg650 inoculated mice was consistent and reproducible, however, one concern was that these results are the product of remaining inoculum as reported by Martin et al [37], or a combination of both de novo generated PrP CWD in these mice, with regards to our results, and remnant inoculum. Nevertheless, our results are in disfavor of a scenario involving a remnant inoculum alone.…”
Section: Discussionsupporting
confidence: 91%
“…The modified RT-QuIC protocol with substrate replacement used here allowed us to ensure the availability of rPrP substrate for a longer period of time to enable the detection of low levels of prion seeding activity that would have been missed otherwise. Positive seeding activity observed in the brain of 77.7% of Wisc-1-tg650 inoculated mice was consistent and reproducible, however, one concern was that these results are the product of remaining inoculum as reported by Martin et al [37], or a combination of both de novo generated PrP CWD in these mice, with regards to our results, and remnant inoculum. Nevertheless, our results are in disfavor of a scenario involving a remnant inoculum alone.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, positive seeding activity observed in the brain of 77.7% of Wisc-1-tg650 inoculated mice was consistent and reproducible, however, one concern was that these results are the product of remaining inoculum as reported by Martin et al 47 , or a combination of both de novo generated PrP CWD in these mice, with regards to our results, and remnant inoculum. Nevertheless, our results are in disfavor of a scenario involving a remnant inoculum alone.…”
Section: Discussionsupporting
confidence: 90%
“…It would be interesting to see how many of these samples would be positive when examined by RT-QuIC. It has also been reported that seeding activity can remain for long periods of time even in PrP knockout mice 27 . Although it should be cautious to compare the phenomenon in cultured cells in this study to latent prion infection at the individual level, it is important to better understand the pathological significance of a condition in which seeding activity can be maintained for a long period of time even when PrP-res is negative.…”
Section: Discussionmentioning
confidence: 96%